Fetal weight projection model to define growth velocity and validation against pregnancy outcome in a cohort of serially scanned pregnancies. (8th June 2022) - Hugh, O.; Gardosi, J.
ABSTRACT: Objective: Fetal growth assessment is central to good antenatal care, yet there is a lack of definition of normal and abnormal fetal growth rate which can identify pregnancies at risk of adverse outcome. The aim of this study was to develop and test a model for defining normal limits of growth velocity which are specific to the fetal weight measurement interval. Methods: The cohort consisted of 102 138 singleton pregnancies which underwent at least two third‐trimester measurements of ultrasound estimated fetal weight (EFW), usually carried out because routine early‐pregnancy risk assessment had indicated an increased risk of fetal growth restriction. We projected the EFW from the first of each consecutive measurement pair along its own centile rank to the gestational age of the second scan. Normal growth was defined as the second EFW being within a weight range based on limits derived by partial receiver‐operating‐characteristics‐curve (pROC) analyses for small‐for‐gestational‐age (SGA; < 10 th  centile) and large‐for‐gestational‐age (LGA; > 90 th  centile) birth weight. The limits were measurement‐interval specific and calculated for a fixed false‐positive rate (FPR) of 10%. The resultant normal, slow and accelerated growth rates calculated from consecutive EFW pairs were evaluated against the following predefined perinatal outcome measures: stillbirth, neonatal death, SGA and LGA at birth, 5‐min Apgar score < 7 and admission to the neonatal intensive care unit. Slow growth based on the last two scans was compared with SGA fetal weight (EFW < 10 th  centile) at the last scan and association with stillbirth risk was assessed, expressed as relative risk (RR) with 95% CI. Results: The optimal cut‐off limits for normal growth rate between consecutive scans varied according to the length of the measurement interval, with an average of –8.0% for slow growth and + 9.3% for accelerated growth at a fixed FPR of 10%. Slow growth between random consecutive scan pairs was associated significantly with all predefined outcome measures including stillbirth (RR, 2.19; 95% CI, 1.84–2.53) and neonatal death (RR, 2.28; 95% CI, 1.60–3.13). Accelerated growth was associated with LGA at birth (RR, 2.15; 95% CI, 2.10–2.20), while normal growth was protective of all adverse outcome measures. Slow growth between the last two scans (which were performed at a median gestational age of 33 + 1 to 36 + 4 weeks) and SGA at the last scan were each predictors of stillbirth, and stillbirth risk was highest when both were present (RR, 2.65; 95% CI, 1.67–4.20). However, 66.2% of pregnancies with slow growth were not SGA at the last scan and these cases also had an increased risk of stillbirth (RR, 2.07; 95% CI, 1.40–3.05). Conclusion: Fetal growth velocity defined by projected, measurement‐interval specific fetal weight limits is associated independently with perinatal outcome and should be used for antenatal surveillance in addition to assessment by fetal size. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.